New generation sequencing: molecular approaches for the detection and monitoring of bioaerosols in an indoor environment: a systematic review - Onwusereaka, Cynthia Oluchi; Jalaludin, Juliana; Oluchi, Sampson Emilia; Poh Choo, Veronica Chua (Walter de Gruyter GmbH, 2024)
Introduction: The exposure of occupants to indoor air pollutants has increased in recent decades. The aim of this review is to discuss an overview of new approaches that are used to study fungal aerosols. Thus, this motivation was to compensate the gaps caused by the use of only traditional approaches in the study of fungal exposure. Content: The search involved various databases such as; Science Direct, PubMed, SAGE, Springer Link, EBCOHOST, MEDLINE, CINAHL, Cochrane library, Web of Science and Wiley Online Library. It was limited to full text research articles that reported the use of non-viable method in assessing bioaerosol, written in English Language, full text publications and published from year 2015–2022. Summary and Outlook: A total of 15 articles met the inclusion criteria and was included in this review. The use of nextgeneration sequencing, which is more commonly referred to as high-throughput sequencing (HTS) or molecular methods in microbial studies is based on the detection of genetic material of organisms present in a given sample. Applying these methods to different environments permitted the identification of the microorganisms present, and a better comprehension of the environmental impacts and ecological roles of microbial communities. Based on the reviewed articles, there is evidence that dust samples harbour a high diversity of human-associated bacteria and fungi. Molecular methods such as next generation sequencing are reliable tools for identifying and tracking the bacterial and fungal diversity in dust samples using 18S metagenomics approach.